2006
DOI: 10.4015/s1016237206000221
|View full text |Cite
|
Sign up to set email alerts
|

Wheeze Recognition Based on 2d Bilateral Filtering of Spectrogram

Abstract: ABSTRACT

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
26
0
2

Year Published

2012
2012
2022
2022

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 39 publications
(30 citation statements)
references
References 22 publications
2
26
0
2
Order By: Relevance
“…By the way, the 8 KHz sampling rate of telephone and VoIP has been evaluated to record wheezing sound well. The sampling rate of the study was identified and supported the results of our previous studies [8][9][10][11].…”
Section: Discussionsupporting
confidence: 80%
See 3 more Smart Citations
“…By the way, the 8 KHz sampling rate of telephone and VoIP has been evaluated to record wheezing sound well. The sampling rate of the study was identified and supported the results of our previous studies [8][9][10][11].…”
Section: Discussionsupporting
confidence: 80%
“…By the way, the 8 KHz sampling rate of telephone and VoIP has been evaluated to record wheezing sound well. The sampling rate of the study was identified and supported the results of our previous studies [8][9][10][11]. In addition the reasons of noises in physiologic signals are usually band-limited, therefore, the optimal sampling frequency can be used to simplify the system design.…”
Section: Discussionsupporting
confidence: 70%
See 2 more Smart Citations
“…If the smoothing kernel is quite large, the detrimental effect is reduction in the detection accuracy, especially at low SNR. Meanwhile, the authors in [24] passed the spectrogram through 2D bilateral filter to reduce noise and preserve its patterns edges. The filtered spectrogram is sent to two parallel processing paths, at which the first path extracts significant patterns from background noise.…”
Section: Related Workmentioning
confidence: 99%